MECHANICAL CHARACTERISTICS OF PET FIBER CONCRETE UNDER SHORT-TERM COMPRESSION - Bilozir, В. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
The study aimed to investigate the effect of the volume percentage of PET fiber reinforcement on the strength and deformability of fine-grained concrete under short-term compression. The research adopted a complete two-factor experiment resulting in a regression equation for calculating the compressive strength of PET fiber concrete. The research used fine-grained concrete of classes C20/25 and C30/35 as the matrix concrete, which is commonly used in structures without prestressing the rods. The research used fiber with dimensions of 40 × 3 × 0.2 mm as a dispersive reinforcement, and the coefficients of PET fiber reinforcement were taken as fv = 0.01 and fv = 0.03. The strength and deformability of PET fiber concrete under short-term compression were tested by testing 100 × 100 × 400 mm prisms. To obtain concrete class C20/25, based on 1 m3, the following composition was adopted: cement PrJSC «Ivano-Frankivskcement» brand M400 with an activity of 42.3 MPa – 444.5 kg; sand with a grain size module of 2.1 from the Yasinetsky quarry – 1644.4 kg; water – 239.2 l. To obtain concrete class C30/35 based on 1 m3, the following composition was adopted: cement PJSC «Ivano-Frankivskcement» brand M500 with an activity of 53.1 MPa – 433.2 kg; sand with a grain size module of 2.1 from the Yasinetsky quarry – 1724.3 kg; water – 215.6 l. The study found that increasing the percentage of fiber reinforcement leads to an increase in the strength of PET fiber concrete, the initial modulus of elasticity of PET fiber concrete, and a reduction in relative deformations at a specific stress intensity. The study proposed a mathematical model for determining the strength of PET fiber concrete based on a planned experiment. The author specified the formula for calculating the strength of PET fiber concrete, which was previously used to calculate the compressive strength of steel fiber concrete. The study also indicated the expediency of using the norm formula for designing reinforced concrete structures to describe the «stress – relative deformations» diagram of PET fiber concrete under short-term compression.